The Effect of Molecular Imprinting on the Loading and Release of Poorly Water Soluble Drug in Hydrogel Gontact Lenses - AL-SHOHANI, Athmar Dhahir Habeeb; Zahraa Yahya Sabri (Iraqi Journal of Pharmaceutical Sciences, 2023)
Therapeutic contact lenses TCLs is an approach used to enhance corneal residence time and reduce frequent instillation, which is a problem with eye drops. The problem with CLs is loading of hydrophobic drugs. In this research the CLs were prepared with molecular imprinting MI to enhance the loading of itraconazole, which is used as antifungal drug for fungal keratitis. CLs using different concentration of hydroxyethyl methacrylate HEMA and methacrylic acid MAA were prepared with and without MI using PEGDA (25 μL) and AIBN (37 mg) as crosslinker and initiator respectively. All the prepared CLs were clear and have good folding endurance. MICLs had significantly higher drug loading compared to conventional CLs. The release of itraconazole from MICLs was sustained compared to conventional CLs. The optimum formula chosen had 8% MAA due to maximum drug loading (1077 μg) compared to non-MI (288 μg) and sustained release for more than 24 h. MI was successfully utilized as a tool to enhance the loading of poorly water soluble drug into a hydrogel CL.